Identifikasi dan Komposisi Hasil Tangkapan Ikan dengan Alat Tangkap Mini Purse Seine di Pesisir Kubutambahan, Bali - Purwanto, Riska; Pertami, Nyoman Dati; Negara, I Ketut Wija (Journal of Marine Research and Technology, 2023)
Kubutambahan Village is one of the villages in Kubutambahan Subdistrict, Buleleng Regency with the main catch fishery potential of Mackerel scad and several other species of fish. The fishing gear used by fishermen is dominated by mini purse seine. The purpose of this research was to determine the types of fish caught and the composition of fish catches. This research was conducted from September 2021 until October 2021. The data were obtained by direct observation in the field. Fish samples were taken using simple random sampling. The results showed that there were 20 species of fish, grouped into 5 orders, 9 families and 16 genera. The composition of the catches of fishermen using mini purse seine is dominated by Mackerel scad at 48.4% and the lowest is Hound Needlefish at 0.001% of overall catch.